OPTIMASI DAN FORMULASI SABUN MANDI CAIR UNTUK BAYI DARI MINYAK BUAH ALPUKAT (PERSEA AMERICANA MILL) - Yuyun Darma Ayu Ningrum; Widyaningrum, Naniek; Sholeh, Aries Badrus; Aprilianti, Yunita (Jurnal Insan Farmasi Indonesia, 2024)
Halal guarantees are implemented to provide comfort, security and peace of mind for people when using halal products. The active ingredient used in this research is avocado oil (Persea Americana Mill). The formula in this research was determined using the Simple Lattice Design (SLD) method with a True Experimental Laboratory research design. In this research, several tests were carried out on the physical properties of the preparation, namely organoleptic test, pH test, foam stability test, viscosity test and homogeneity test. Based on the recommended simple lattice design (SLD) method, data from 10 evaluation tests of formulation preparations were tested and an optimal formulation was obtained. This formula contains a concentration of 12.5% coconut oil and 17.5% KOH. Overall, the physical evaluation of liquid soap formulations in this study shows that R1, R2, and R3 meet the requirements for baby liquid soap according to established standards. The liquid soap for babies obtained from this research has a characteristic liquid consistency, is yellowish white in color and has a distinctive odor. The achieved pH value, foam stability, viscosity and homogeneity are in accordance with established standards.